Injury rates in Iranian taekwondo athletes; a prospective study - Ziaee, V.; Rahmani, S.-H.; Rostami, M. (Asian Journal of Sports Medicine, 2010)
Taekwondo, as the most popular martial art among Iranian sportsmen, might lead to injury for the athletes of this sport during competitions. We decided to report the incidence rate of injuries sustained by the athletes of this sport during national competitions.